System dynamics for the water footprint assessment and simulation in the bioethanol production. (2018) - Trujillo-Mata, Armin; Cortés-Robles, Guillermo; Sánchez-Ramírez, Cuauhtémoc; Blanco-Fernández, Julio; Jiménez-Macías, Emilio
The bioethanol industry is one of the growing sectors worldwide which is seeking for sustainability along its supply chain. The increasing demand for bioethanol makes this industry face a conflict: to increase productivity without compromising the future natural resources such as water. This work proposes to integrate the water footprint assessment methodology to the supply chain analysis using system dynamics. In this paper, the application of the synergy is to assess and simulate the water footprint of the bioethanol production stages using the system dynamics methodology. System dynamics could be a useful approach to model and simulate the water footprint of bioethanol supply chain and estimate its impact on water resources for the succeeding years.